Experimental investigation into methane hydrate production during three-dimensional thermal stimulation with five-spot well system - Wang, Yi; Li, Xiao-Sen; Li, Gang; Zhang, Yu; Li, Bo; Chen, Zhao-Yang (Applied Energy, 2013)
The cubic hydrate simulator (CHS) is used to study the methane hydrate production behaviors in porous media by the thermal stimulation with a five-spot well system. The hot water injection rates range from 10.0 to 40.0 ml/min. The thermal stimulation process is analyzed, and the conclusions are that the hydrate decomposition boundary moves from the central point to the surroundings gradually and finally covers almost the entire hydrate field in the CHS during the thermal stimulation process. The heat conduction plays a more significant role than the convection for the heat diffusion in the thermal stimulation process. The increasing injection rate of the hot water enhances the rate of hydrate decomposition, shortens the production time, and decreases the water production volumes, while it has little influence on the final gas production volumes. Furthermore, the change of the hot water injection rate (R-inj)has little influence on the final gas recovery, however, the higher R-inj leads to the higher average production rate and the lower energy efficiency. (C) 2013 Elsevier Ltd. All rights reserved.